Basin-wide water accounting based on remote sensing data: an application for the Indus Basin - Karimi, Poolad; Bastiaanssen, Wim G.M.; Molden, David J.; Cheema, Muhammad Jehanzeb Masud (Copernicus GmbH, 2013)
The paper demonstrates the application of a new water accounting plus (WA+) framework to produce information on depletion of water resources, storage change, and land and water productivity in the Indus basin. It shows how satellite-derived estimates of land use, rainfall, evaporation (E), transpiration (T ), interception (I ) and biomass production can be used in addition to measured basin outflow, for water accounting with WA+. It is demonstrated how the accounting results can be interpreted to identify existing issues and examine solutions for the future. The results for one selected year (2007) showed that total annual water depletion in the basin (501 km3) plus outflows (21 km3) exceeded total precipitation (482 km3). The water storage systems that were effected are groundwater storage (30 km3), surface water storage (9 km3), and glaciers and snow storage (2 km3). Evapotranspiration of rainfall or "landscape ET? was 344 km3 (69% of total depletion). "Incremental ET? due to utilized flow was 157 km3 (31% of total depletion). Agriculture depleted 297 km3, or 59% of the total depletion, of which 85% (254 km3) was through irrigated agriculture and the remaining 15% (44 km3) through rainfed systems. Due to excessive soil evaporation in agricultural areas, half of all water depletion in the basin was non-beneficial. Based on the results of this accounting exercise loss of storage, low beneficial depletion, and low land and water productivity were identified as the main water resources management issues. Future scenarios to address these issues were chosen and their impacts on the Indus Basin water accounts were tested using the new WA+ framework.